Taking Lacquer as a Mirror, Expressing Morality via Implements: A Study of Confucian Ritual Spirituality and the Concept of Consumption in the Ming and Qing Dynasties - Fan, Kuo-Kuang (Religions, 2020)
The periods of the Ming and Qing dynasties featured prosperous socioeconomic development; the development of industrial, commercial, and manufacturing production; and active urban consumer behavior with great advocacy for the doctrines of Confucius and Mencius in the imperial court, and extensive promotion of refined elegance of benevolence, righteousness, ritual, and wisdom among the public. Under the influence of such an objective environment, lacquerware, as China’s most ancient traditional form of artwork, also functioned as significant historical evidence for the development of the urban handicraft industry. Assuming a social role between ritual items and daily items, the development of lacquer arts was closely bound up with Confucian ritual spirituality. Based on relevant cultural relic data and documents in the literature, this study takes lacquer as a mirror with regard to the progress of the trend of lacquer culture and lacquer art during the Ming and Qing dynasties as the clue, and analyzes the embodied features of lacquer art design function, modeling, and themes to discuss the influence of Confucian ritual spirituality on social consumption.